2021
DOI: 10.2217/fon-2020-0572
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Their Implications on Quality of Life and Psychological Distress in Sarcoma Patients

Abstract: The aim of this study was to investigate symptoms, their variation over time and their relationship with quality of life (QoL)/psychological distress in sarcoma patients, as few data regarding QoL and psychological distress in this set of patients are currently available. A total of 188 sarcoma patients from an Italian referral center were involved. Symptoms and financial difficulties were evaluated with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire from the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The current study showed that somatic symptoms, either by affecting functional status or by causing psychological distress, negatively affect extremity STS patients' QoL. 21,25,26 Thus, relieving pain and other somatic symptoms in STS patients may alleviate the patients' distress and enhance their HRQL. Comparing to the other chronic debilitating diseases, the psychological burden of somatic symptoms are more prominent in advanced STS.…”
Section: Physical Functioningmentioning
confidence: 67%
See 4 more Smart Citations
“…The current study showed that somatic symptoms, either by affecting functional status or by causing psychological distress, negatively affect extremity STS patients' QoL. 21,25,26 Thus, relieving pain and other somatic symptoms in STS patients may alleviate the patients' distress and enhance their HRQL. Comparing to the other chronic debilitating diseases, the psychological burden of somatic symptoms are more prominent in advanced STS.…”
Section: Physical Functioningmentioning
confidence: 67%
“…The most common somatic symptoms experienced by the patients were fatigue and pain although the sources of pain varied. Lack of appetite, constipation, and lack of concentration were other symptoms experienced in STS 21,25 . Along with their adverse functional impact, somatic symptoms were associated with psychological distress and lower QoL in extremity STS patients 21,25,26 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations